Hepatic arterial infusion chemotherapy combined with lenvatinib and toripalimab for large hepatocellular carcinoma (> 10 cm) with major portal vein tumor thrombosis: a multicenter propensity score matching analysis - Li, Yangyang; Wang, Danchen; Zhang, Fengtao; Zheng, Xiang; Song, Yipei; Ran, Yang; Cai, Xiangran (Frontiers in Immunology, 2025)
BackgroundPortal vein main trunk tumor thrombus is one of the most intractable complications of hepatocellular carcinoma(HCC), often occurring in patients with high intrahepatic tumor burden(>10 cm). High tumor burden HCC complicated by portal vein main trunk tumor thrombus is regarded as the very advanced stage with extremely poor therapeutic efficacy and very limited treatment options and its long-term survival depends on the dual remission of intra-hepatic tumors and tumor thrombi. Previous phase III trials have confirmed the ability of HAIC to effectively relieve high tumor burden HCC, yet HAIC alone cannot effectively manage tumor thrombi and intrahepatic progression. The efficacy of the combination of HAIC, lenvatinib and toripalimab in advanced HCC has also been confirmed by existing clinical evidence. Therefore, the combination of HAIC, lenvatinib and toripalimab may be a potentially effective treatment regimen for high tumor burden HCC complicated by portal vein main trunk tumor thrombus.MethodsA retrospective review was conducted on the clinical data of patients with high tumor burden HCC complicated by main portal vein tumor thrombus who received HAIC combined with lenvatinib and toripalimab(HAICLT group) or HAIC alone(HAIC group) from August 2019 to December 2023. Propensity score matching was employed to balance the baseline differences between the groups. The overall survival time, progression-free survival time, objective response rate, and disease control rate were compared between the groups.ResultsAfter PSM, the median OS and median PFS of the HAICLT group were 21.2 months and 7.4 months respectively, significantly better than 6.6 months(HR: 0.35; 95% CI: 0.22-0.56, P < 0.001) and 3.0 months(HR: 0.45; 95% CI: 0.31-0.66, P < 0.001) of the HAIC group. In terms of treatment response, the HAICLT group also accomplished higher rates of intrahepatic responses(ORR: 57.7% vs 19.7%, P<0.001; DCR: 91.5% vs 59.2%, P<0.001) and PVTT responses(ORR: 62.0% vs 21.1%, P<0.001; DCR: 93.0% vs 50.7%, P<0.001) compared to the HAIC group. No significant statistical differences were found in the incidence rates of adverse events at all grades and grades 3–4 between the groups.ConclusionCompared with HAIC alone, the combination of HAIC, lenvatinib, and toripalimab can effectively prolong the survival prognosis of patients with large HCC complicated by major PVTT and achieve intrahepatic and PVTT remission. It is a promising treatment approach.